Hospitalization among street-involved youth who use illicit drugs in Vancouver, Canada: a longitudinal analysis - Derek C. Chang; Launette Rieb; Ekaterina Nosova; Yang Liu; Thomas Kerr; Kora DeBeck (BMC, 2018)
Abstract Background Street-involved youth who use illicit drugs are at high risk for health-related harms; however, the profile of youth at greatest risk of hospitalization has not been well described. We sought to characterize hospitalization among street-involved youth who use illicit drugs and identify the most frequent medical reasons for hospitalization among this population. Methods From January 2005 to May 2016, data were collected from the At-Risk Youth Study (ARYS), a prospective cohort study of street-involved youth in Vancouver, Canada. Multivariable generalized estimating equation (GEE) was used to identify factors associated with hospitalization. Results Among 1216 participants, 373 (30.7%) individuals reported hospitalization in the previous 6 months at some point during the study period. The top three reported medical reasons for hospital admission were the following: mental illness (37.77%), physical trauma (12.77%), and drug-related issues (12.59%). Factors significantly associated with hospitalization were the following: past diagnosis of a mental illness (adjusted odds ratio [AOR] = 1.85; 95% confidence interval [95% CI] 1.47-2.33), frequent cocaine use (AOR = 2.15; 95% CI 1.37-3.37), non-fatal overdose (AOR = 1.76; 95% CI 1.37-2.25), and homelessness (AOR = 1.40; 95% CI 1.16-1.68) (all p < 0.05). Conclusions Findings suggest that mental illness is a key driver of hospitalization among our sample. Comprehensive approaches to mental health and substance use in addition to stable housing offer promising opportunities to decrease hospitalization among this vulnerable population.